Fertility Response Following Two Estrus Synchronization Protocols in Anestrus Beetal Goats - Kamra, Abhi; Honparkhe, Mrigank; Bisla, Amarjeet; Kumar, Ajeet; Singla, Mandeep; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2026)
This study evaluated the comparative efficacy of GnRH and eCG-based estrus synchronization protocols with or without short-term progesterone in postpartum anestrus Beetal goats. Twenty goats were administered Buserelin acetate (6 µg IM, day 0) and randomly allocated to a progesterone group (TRIU-B, 400 mg; n=10, Group I) or a non-progesterone group (n=10, Group II). On day 7, TRIU-B was removed, and all goats received cloprostenol sodium (75 µg IM) and eCG (400 IU IM). Natural mating after 12h intervals followed estrus detection. Estrus induction was 100% in both groups. Pregnancy (70% vs. 60%) and kidding rates did not differ significantly (P>0.05). However, estrus onset occurred earlier (P
Keywords: Goats; Beetal; Postpartum Anestrus; Fertility; Vaginal mucus electrical resistance